MANEJO DE GIBERELA E MANCHA-AMARELA NA CULTURA DO TRIGO - Telaxka, Fábio Junior (2018)
Silicon has been outstanding without control of plant diseases, increasing resistance in several plant species, mainly in monocotyledonous, whereas B. subtilis, a natural inhabitant of soils, is shown as excellent biocontrol agent of phytopathogens. The objective of this work was to evaluate the potential of Silicon Dioxide (SiO2) and B. subtilis in the control of yellow spot (Drechslera tritici-repentis) and giberela (Gibberella zeae) in wheat. The treatments used for all the experiments were: T1 - SiO2; T2 - B. subtilis; T3 - SiO2 + B. subtilis; T4 - trifloxystrobin + prothioconazole/trifloxystrobin + tebuconazole; T5 - Witness. For field experiments conducted in Virmond and Guarapuava municipalities, the incidence and severity of the diseases were evaluated, being represented by the area under the disease progression curve (AACPDI and AACPDS) in addition to the phytotechnical analysis and the activity of the defense enzymes (polyphenoloxidase and phenylalanine ammonia-lyase). In the municipality of Virmond, all treatments reduced the AACPDS in relation to the control, and the lowest AACPDI of the wheat yellow spot was verified with the treatment based on trifloxystrobin + prothioconazole / trifloxystrobin + tebuconazole, which was 60.2% in relation to the witness, however. For AACPDI of giberela there was no difference between treatments, while the lowest AACPDS was observed with SiO2, B. subtilis, SiO2 + B. subtilis and chemical treatments, which provided a reduction of 29,1, 36%, 40,1% and 45,1%, respectively, relative to the control. All treatments increased the height of plants, number of grains per spikelet and mass of one thousand grains, except the treatment with Silicon Dioxide that presented smaller number of grains per spikelet. The highest activity of the polyphenoloxidase and phenylalanine ammonia lyase enzymes was verified for SiO2 and B. subtilis treatments after 14 days of application. In Guarapuava, for the AACPDI of the yellow spot, the treatments with SiO2, B. subtilis and SiO2 + B. subtilis presented no difference in relation to the control. The treatment that resulted in a lower incidence (61% lower than the control) was the basis of trifloxystrobin + prothioconazole / trifloxystrobin + tebuconazole. For the AACPDS the treatments with B. subtilis and SiO2 resulted in reduction of 73,1% and 74,81%, respectively, in relation to the control. All treatments increased the weight of one thousand seeds and the hectoliter weight in relation to the control. For other phytotechnical variables, the treatments did not provide results with a significant difference in relation to the control. The activity of phenylalanine ammonia-lyase was greater at 14 days after treatment with B. subtilis and SiO2, while for polyphenoloxidase activity, higher activity was observed 24 hours after the fourth application of the treatments. In the in vitro assays the mycelial growth of G. zeae and phytoalexin induction of sorghum, beans and soybean were carried out. For mycelial growth treatment with B. subtilis alone or in combination with SiO2 reduced mycelial growth by 61,4% and 43,4%, respectively. SiO2 has been shown to have a greater eliciting effect, increasing the synthesis of phytoalexins from sorghum and soybean. For the phytoalexin phaseolina of the common bean, neither one of the treatments presented inductive effect of its synthesis. It is concluded that Si and B. subtilis contribute positively to the integrated management of diseases of the wheat crop, interfering in structural and agronomic traits of the plant or the pathogen, as observed in the in vitro tests. Regarding the induction of resistance in plants further studies are needed to clarify such results.